2012
DOI: 10.1007/s11517-011-0859-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the time scale and anatomical location of atrial fibrillation spontaneous termination in a biophysical model

Abstract: Due to their transient nature, spontaneous terminations of atrial fibrillation (AF) are difficult to investigate. Apparently, confounding experimental findings about the time scale of this phenomenon have been reported, with values ranging from 1 s to 1 min. We propose a biophysical modeling approach to study the mechanisms of spontaneous termination in two models of AF with different levels of dynamical complexity. 8 s preceding spontaneous terminations were studied and the evolution of cycle length and wavef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Consistent with the concept of an organized rotor driving AF, it was shown that local catheter ablation may indeed terminate AF by several mechanisms relating to local tissue properties which are increasingly detectable in patients (Rappel et al 2015). Biophysical modeling has also been used to investigate the spontaneous termination of AF, wherein results suggested that termination mechanisms were dependent on the underlying complexity of the arrhythmia (Uldry et al 2012). …”
Section: Non-pharmacological Rhythm-control Therapiesmentioning
confidence: 99%
“…Consistent with the concept of an organized rotor driving AF, it was shown that local catheter ablation may indeed terminate AF by several mechanisms relating to local tissue properties which are increasingly detectable in patients (Rappel et al 2015). Biophysical modeling has also been used to investigate the spontaneous termination of AF, wherein results suggested that termination mechanisms were dependent on the underlying complexity of the arrhythmia (Uldry et al 2012). …”
Section: Non-pharmacological Rhythm-control Therapiesmentioning
confidence: 99%
“…Uldry et al [49] investigated the mechanisms of spontaneous AF termination in two different Conduction is initially blocked from entering the inter-pulmonary region of the left atrium (IPR LA) due to the longer refractory period, and develops into a re-entrant circuit. Colour map represents membrane potential at each node of the anatomical model and arrows indicate wavefront propagation.…”
Section: Termination Of Atrial Fibrillationmentioning
confidence: 99%
“…In silico modeling of atrial fibrillation is adressed e.g. by Aslanidi et al [5] and Uldry et al [6]. A comparison of atrial models published until today is given by Wilhelms et al [7].…”
Section: Introductionmentioning
confidence: 99%